2009
DOI: 10.1530/rep-08-0299
|View full text |Cite
|
Sign up to set email alerts
|

The histone deacetylase inhibitor scriptaid enhances nascent mRNA production and rescues full-term development in cloned inbred mice

Abstract: Since the birth of Cumulina, the first mouse clone produced by somatic cell nuclear transfer (SCNT), the success rate of cloning in mice has been extremely low compared with other species and most of the inbred mouse strains have never been cloned. Recently, our laboratory has found that treatment of SCNT mouse embryos with trichostatin A, a histone deacetylase inhibitor (HDACi), improved the full-term development of B6D2F1 mouse clones significantly. However, this was not effective for the inbred strains. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
118
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(124 citation statements)
references
References 26 publications
3
118
0
1
Order By: Relevance
“…As Lys-5 is the last lysine to be acetylated, acetylated H4K5 reflects hyperacetylated histone H4, and this is correlated with a transcriptionally permissive state of the chromatin (26) that may be a necessary step for the embryonic genome activation occurring at the twocell stage. Indeed, a recent study by Van Thuan et al (27) has shown that Scriptaid, another inhibitor of HDAC, is able to increase the rate of de novo RNA synthesis in SCNT embryos at the two-cell stage. Comparison of the transcriptome profile at one-and two-cell stages in mouse SCNT and fertilized embryos revealed that a large subset of genes is indeed abnormally expressed during the embryonic genome activation (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Lys-5 is the last lysine to be acetylated, acetylated H4K5 reflects hyperacetylated histone H4, and this is correlated with a transcriptionally permissive state of the chromatin (26) that may be a necessary step for the embryonic genome activation occurring at the twocell stage. Indeed, a recent study by Van Thuan et al (27) has shown that Scriptaid, another inhibitor of HDAC, is able to increase the rate of de novo RNA synthesis in SCNT embryos at the two-cell stage. Comparison of the transcriptome profile at one-and two-cell stages in mouse SCNT and fertilized embryos revealed that a large subset of genes is indeed abnormally expressed during the embryonic genome activation (27).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent study by Van Thuan et al (27) has shown that Scriptaid, another inhibitor of HDAC, is able to increase the rate of de novo RNA synthesis in SCNT embryos at the two-cell stage. Comparison of the transcriptome profile at one-and two-cell stages in mouse SCNT and fertilized embryos revealed that a large subset of genes is indeed abnormally expressed during the embryonic genome activation (27). Among them, many transcription factors were found to be either up-regulated or repressed, therefore, affecting the reprogramming of the somatic genome into a totipotent one.…”
Section: Discussionmentioning
confidence: 99%
“…These beneficial effects, corroborated in miniature pig SCNT embryos (Miyoshi et al 2010), have recently been questioned by Ono et al (2010), who compared the effects of different HDACis on cloning BD129F1 mice. The discrepancy of results in the mouse species can be probably attributed to strain-specific differences, as not all HDACis are equally effective in all genetic backgrounds (Kishigami et al 2007, Van Thuan et al 2009). With regard to the IE procedure, although Gasparrini et al (2003) previously reported the production of a cloned mouse using cytoplasts prepared by IE, we were unable to obtain live offspring from the IE group.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, different types of epigenetic modifications can interact with each other (as shown in Figure 2); the abnormality in one type of epigenetic modification must result in the abnormality in other types of epigenetic modifications. For example, due to incomplete DNA demethylation, cloned embryos would exhibit lower level of histone acetylation and H3K4 methylation, and higher level of H3K9 methylation, that is why treatment of cloned embryos with histone deacetylase inhibitor (trichostatin A, sodium butyrate, Scriptaid, and VPA), as well as inducing express of H3K9me3 demethylases JMJD2B, could improve their developmental ability (Rybouchkin et al 2006;Van Thuan et al 2009;Das et al 2010;Xu et al 2012;Antony et al 2013). …”
Section: Main Barricades Of Reprogramming Somatic Cells By Oocytesmentioning
confidence: 99%